Valorisation of rosehip waste into a food ingredient – Focus on its colour, carotenoid content, and techno-functional properties - Alexandra Raluca Borşa (Bogdan); Floricuța Ranga; Melinda Fogarasi; Andrei Borşa; Dan Cristian Vodnar; Cristina Anamaria Semeniuc (Applied Food Research)
Rosehips are rich in nutrients such as dietary fibre and bioactive compounds, including vitamin C, polyphenols, and carotenoids; the waste generated from their industrial processing has the potential to be valorised into a food ingredient. This study proposes an alternative method for preparing rosehip purée, the main ingredient in this jam: cold pressing of rosehips so that as many bioactive compounds as possible remain in the resulting solid waste, which could be valorised as a food ingredient. It aims to evaluate the extent to which this new method (modern) affects certain bioactive compounds in the resulting waste compared to the traditional method (by boiling). To this end, the two wastes generated through the traditional and modern processing of rosehips were hot air- and freeze-dried, and the resulting powders were investigated in terms of colour, carotenoid content and techno-functional properties. The powder prepared by drying the raw waste with hot air showed the most attractive colour, the highest carotenoid content (27.94 µg/g), and good techno-functional properties (WHC-2.48 g/g, OHC-0.93 g/g, SC-5.13 mL/g, solubility-80.82 %). In conclusion, hot air drying the waste generated by cold pressing the rosehips was the most cost-effective food ingredient production method.